High resolution magnetic resonance imaging of atherosclerosis and the response to balloon angioplasty. Issue 2 (1st February 2000) - Coulden, R A; Moss, H; Graves, M J; Lomas, D J; Appleton, D S; Weissberg, P L
Abstract : OBJECTIVE: To explore the use of high resolution magnetic resonance imaging (MRI) of the popliteal artery in defining atheroscelerotic lesions and to monitor the remodelling response to balloon angioplasty. METHODS: Four patients (aged 49–67) with symptomatic discrete popliteal artery stenoses, as demonstrated by conventional angiography, underwent balloon angioplasty. MRI of the diseased vessel was performed before and one week, one month, three months, and six months after therapeutic balloon angioplasty. Cine phase contrast MRI was used to estimate blood flow just proximal to the lesion before and after angioplasty. RESULTS: In all patients the extent of the atherosclerotic plaque could be defined, such that even in segments of vessel which were angiographically "normal", atherosclerotic lesions with cross sectional areas ranging from 49% to 76% of potential lumen area were identified. Following angioplasty, plaque fissuring and local dissection were easily identified and serial changes in lumen diameter, blood flow. and lesion size could be documented. CONCLUSIONS: High resolution MRI can define the extent of atherosclerotic plaque in the peripheral vasculature and demonstrate the changes that occur with remodelling and restenosis following angioplasty. As a safe, reproducible technique MRI is ideal for assessing plaque and monitoring intervention, but further technological developments will be needed if similar or better images are to be achieved in other vascular beds.